A micro perspective on r > g. (14th February 2023) - Iacono, Roberto; Palagi, Elisa
Abstract: By exploiting large‐scale administrative data on income and estimated personal wealth in Norway from 2010 to 2018, this paper establishes the first micro‐level analysis of the difference between the real return on wealth and the real growth rate of total pre‐tax income, across the entire net wealth distribution. We show that for the top 40% of the distribution, the aggregate R − G R-G of 1.8% underestimates its micro counterpart r − g r-g , while the opposite happens for the bottom 60%. Moreover, for the bottom 50% of the net wealth distribution, it is indeed the case that r < g r<g . In addition, we run a simulation exercise demonstrating that the full distribution of r − g r-g —which has been shown to be positively associated with the position in the net wealth distribution—delivers a higher predictive power for the study of wealth inequality than simply focusing on the aggregate R − G R-G . All results are robust to the exclusion of imputed rents from the income definition.